Teaching Media Literacy in Grade Five: The Development of Technological Literacy Among Teachers and Students - A Case Study - Rachel McCabe; Winston Emery (The Canadian Network for Innovation in Education (CNIE), 2003)
This is the second of two articles about a study of the implementation of a media literacy curriculum project in three inner city schools Grade 5's in Montreal. The authors describe the development of technological literacy among the teachers and students as they learned about two Media Literacy concepts. The teaching featured the use of a SMARTboard interface, a list-serv and Web resources. The findings affirm the positive contribution of the devices to the development of technological literacy among teachers and pupils. But they also raise other issues: technological determinism and the role of interpretive teaching in educational technology.